Bisa Bea, bisa Bel - Machado, Ana Maria, 1941-; Marco, Vicent; Andreu, Fatima (Mexico, D.F. : Fondo de Cultura Economica, 1997)
Isabel is enchanted with an old photograph of her great-grandmother, taken when she was about Isabel's age. An imaginary dialogue develops between the two and from the mixture of the two generations with their differing points of view, clothes and lifestyles, a new personage emerges. A picture of life in Brazil is given through the eyes of Isabel and her great-grandmother.
"Para los que leen bien"--P. [4] of cover.
Translation of: Bisa Bia, Bisa Bel.
007-009.
Keywords: Great-grandmothers -- Fiction; Conflict of generations -- Fiction; Brazil -- Fiction